Hubungan Persepsi Siswa Tentang Pelaksanaan Tata Tertib Sekolah Dengan Sikap Disiplin Siswa SMA Muhammadiyah 1 Surakarta - Anisa Indriyani; Dhian Rizkiana Putri (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Discipline is a very important attitude for every person to have in order to be accepted in society. Of the many positive impacts that a person gets by being disciplined, of course there are also negative impacts that arise if they are not disciplined in an environment. The reason someone is not disciplined is because of their negative perception of those rules. So, so that students can comply with school rules, they must have a positive perception of the rules, so that a disciplined attitude will be formed in students. This research aims to determine the relationship between students' perceptions regarding the implementation of school rules and discipline attitudes of students at SMA Muhammadiyah 1 Surakarta. This research uses a quantitative type of research. The population in this study were students of SMA Muhammadiyah 1 Surakarta, while the sample in this study was students of class XI SMA Muhammadiyah 1 Surakarta. The research results show that there is a significant relationship between student perceptions and student disciplinary attitudes. This can be seen from the correlation test results of 0.566 with a significance level (p) of 0.000 (p < 0.01) from the r table of 0.138 which states that the hypothesis is accepted.